Konflik Yurisdiksi Antara Pengadilan Kriminal Internasional Dan Pengadilan Hibrid: Analisis Kesenjangan Normatif - Muhammad Fajar Lutfi Raihan; Amos Saito Hamonangan Simorangkir; Rivaldi Julianto Ardiansyah (GLOBAL SCIENTS PUBLISHER, 2026)
The existence of two international criminal justice regimes: the permanent International Criminal Court (ICC) and the ad hoc hybrid courts, has given rise to complex and unresolved jurisdictional issues in the contemporary international legal order. This article critically examines the jurisdictional conflict arising between these two mechanisms, with an emphasis on identifying and analyzing the normative gaps underlying the problem. This research employs a juridical-normative approach based on literature review, analyzing primary international legal instruments such as the 1998 Rome Statute, treaties establishing various hybrid courts, and relevant judicial decisions. The research findings indicate that the most significant normative gaps lie in: (1) the absence of a clear jurisdictional hierarchy in international law; (2) inconsistent application of the complementarity principle; (3) differences in procedural and substantive legal standards between institutions; and (4) the inadequacy of existing inter-institutional coordination mechanisms. This article argues that resolving such conflicts requires structural normative reform, not merely partial technical adjustments. Drawing on the experiences of the Special Court for Sierra Leone and the Extraordinary Chambers in the Courts of Cambodia, this study recommends the establishment of a legally binding jurisdictional coordination protocol between the ICC and future hybrid courts.